Approximating the Least-Squares Bias in Multiple Regression with Errors in Variables - Blomqvist, A. G. (The Review of Economics and Statistics, 1972)
imports, where quoted import price indexes are used to avoid serious measurement errors and information on changes in the variables over years is utilizecl. It has been found that the elasticity is numerically larger for finished goods than for crude materials and intermediate goods. Effects of time lags are different between commodity types; in the case of finished goods, adjustment to price changes seem to be completed within a year, but for materials or intermediate goods, adjustment seems to take longer. There is an evidence, which is not very strong, that shows that the progressive trade liberalization that has taken place in Japan has worked to increase the numerical value of the elasticity of substitution.